Why do urbanites travel more than do others? A review of associations between urban form and long-distance leisure travel - Michał Czepkiewicz; Jukka Heinonen; Juudit Ottelin (Environmental Research Letters, 2018)
Negative relationships between urban density and greenhouse gas emissions from daily travel are well established in the literature. However, recent research suggests that higher urban density is associated with higher emissions from long-distance leisure travel, such as car weekend trips and international flights. This article presents the first systematic review of empirical evidence on these associations and discusses potential explanations. A two-step article selection process yielded 27 empirical articles, complemented by one article published during the review process. When international travel is included in the analysis, the results suggest that residents of the largest cities, and particularly those from centrally located and densely built areas, travel more to cover long distances than do others, after controlling for demographic and socioeconomic variables. When only domestic travel is included, residents of larger settlements and areas of higher density engage in less long-distance travel for leisure purposes than those living in smaller settlements and sparsely built areas. The results of the review are indicative and warrant more research. Generalization is currently limited because of the wide variety of travel behavior measures used, consideration of different travel modes and trip purposes, and geographic scope. There is a strong need for replication of the results using consistent methodology, using data from longer and more recent time spans, and expanding to more diverse geographical settings, especially outside Europe. The systematic review is followed by a narrative review of theoretical explanations of the associations. The most common explanations include: rebound effects, the compensation hypothesis, access to transport infrastructure, urban lifestyles, sociopsychological characteristics, and social networks. Socioeconomic variables are controlled in a majority of the reviewed studies, and business travel is excluded from the review, so the concentration of wealth and business in cities may explain the findings only to some extent. Nonetheless, there is not enough empirical evidence on the causal character of the associations and therefore further qualitative and multidisciplinary work is needed. Compact city and urban densification policies are not strongly challenged by current evidence, and most common policy recommendations point to including air travel into carbon taxing or quota schemes.